2012
DOI: 10.1038/ismej.2012.104
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome composition is linked to whole grain-induced immunological improvements

Abstract: The involvement of the gut microbiota in metabolic disorders, and the ability of whole grains to affect both host metabolism and gut microbial ecology, suggest that some benefits of whole grains are mediated through their effects on the gut microbiome. Nutritional studies that assess the effect of whole grains on both the gut microbiome and human physiology are needed. We conducted a randomized cross-over trial with four-week treatments in which 28 healthy humans consumed a daily dose of 60 g of whole-grain ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
334
6
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 494 publications
(380 citation statements)
references
References 67 publications
26
334
6
4
Order By: Relevance
“…The mechanisms responsible could be alterations to gut microbiota improving systemic inflammation independently of weight loss [29], altered digestion and/or absorption of protein subsequently affecting Changes at the end of the intervention period have been compared with the end of the runin period/baseline assessment using Student's t test for paired samples; not-normally distributed values were log e -transformed. *p<0.05, **p<0.01, ***p<0.001 the amino acid profile [12], or altered rates of colonic fermentation with production of short-chain FA [29]. Chronic coffee consumption has been reported to have similar effects [30].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms responsible could be alterations to gut microbiota improving systemic inflammation independently of weight loss [29], altered digestion and/or absorption of protein subsequently affecting Changes at the end of the intervention period have been compared with the end of the runin period/baseline assessment using Student's t test for paired samples; not-normally distributed values were log e -transformed. *p<0.05, **p<0.01, ***p<0.001 the amino acid profile [12], or altered rates of colonic fermentation with production of short-chain FA [29]. Chronic coffee consumption has been reported to have similar effects [30].…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of Ruminococcaceae in centenarians has been reported, with a positive correlation with high-fiber diets (39) and after intervention with resistant starch (40). Furthermore, in the study by Martínez et al, Ruminococcaceae were more dominant in normoweight than obese individuals and negatively correlated with markers of inflammation (41). A lower abundance of this taxon was associated with exaggerated Toll-like receptor 2 (TLR-2) responses and an increased risk of developing IgE-associated eczema in infants (42).…”
Section: Discussionmentioning
confidence: 89%
“…Uncultured representatives of the class Coriobacteriia have been correlated with host lipid metabolism in human (Lahti et al, 2013) and animal (Martínez et al, 2009(Martínez et al, , 2013Claus et al, 2011) studies, andHoyles (2009) suggested that Col. aerofaciens plays a role in lipid metabolism within the large intestine. As such, the resuscitatable (217/224) faecal 'Atopobium cluster' isolates were assayed for lipase activity using olive oil/rhodamine B agar as described by Hoyles (2009), with Staphylococcus aureus (positive) and Escherichia coli (negative) used as controls.…”
Section: T Thorasin L Hoyles and A L Mccartneymentioning
confidence: 99%